Deficiency in AMPK attenuates ethanol-induced cardiac contractile dysfunction through inhibition of autophagosome formation - Guo, Rui (Oxford University Press, 2012)
AIMS: Binge drinking often triggers compromised myocardial contractile function while activating AMP-activated protein kinase (AMPK). Given the role of AMPK in the initiation of autophagy through the mammalian target of rapamycin complex 1 (mTORC1) and Unc51-like kinase (ULK1), this study was designed to examine the impact of AMPK deficiency on cardiac function and the mechanism involved with a focus on autophagy following an acute ethanol challenge. METHODS AND RESULTS: Wild-type (WT) and transgenic mice overexpressing a kinase-dead (KD) α2 isoform (K45R mutation) of AMPK were challenged with ethanol. Glucose tolerance, echocardiography, Langendorff heart and cardiomyocyte contractile function, autophagy, and autophagic signalling including AMPK, acetyl-CoA carboxylase (ACC), mTOR, the mTORC1-associated protein Raptor, and ULK1 were examined. Ethanol exposure triggered glucose intolerance and compromised cardiac contraction accompanied by increased phosphorylation of AMPK and ACC as well as autophagosome accumulation (increased LC3II and p62), the effects of which were attenuated or mitigated by AMPK deficiency or inhibition. Ethanol dampened and stimulated, respectively, the phosphorylation of mTOR and Raptor, the effects of which were abolished by AMPK deficiency. ULK1 phosphorylation at Ser(757) and Ser(777) was down-regulated and up-regulated, respectively, by ethanol, the effect of which was nullified by AMPK deficiency or inhibition. Moreover, the ethanol challenge enhanced LC3 puncta in H9c2 cells and promoted cardiac contractile dysfunction, and these effects were ablated by the inhibition of autophagy or AMPK. Lysosomal inhibition failed to accentuate ethanol-induced increases in LC3II and p62. CONCLUSION: In summary, these data suggest that ethanol exposure may trigger myocardial dysfunction through a mechanism associated with AMPK-mTORC1-ULK1-mediated autophagy.